PENGEMBANGAN SISTEM PENGELOLAAN LAUNDRY BERBASIS WEB (STUDI KASUS ARIN LAUNDRY) - Angga Dwi Putra; Dwi Sakethi; Ardiansyah Ardiansyah (Jurnal Pepadun, 2021)
Arin Laundry is a laundry service business located in Gedong Tataan, Pesawaran Regency, Lampung Province. Management of business activities at Arin Laundry still uses the old method, namely the manual method. Therefore, this research was conducted to build an information system that can help Arin Laundry in running its business, so that business management at Arin Laundry can run well. The business management includes transactions, user management, laundry type management, expenses, monitoring of laundry raw materials, expense and income reports, bar graph reports, profit reports, and sending SMS notifications to customers so that customers can know for sure that the laundry belongs to the customer. have been completed. SMS notifications can also inform customers that washing is being picked up and being delivered. In the development of information systems, a system development method is applied, namely the waterfall method developed in conjunction with the PHP and MySQL programming languages and using the Laravel framework. System testing is carried out using black box testing, namely by observing the results of execution through test data and checking the functionality contained in the system. This research has succeeded in developing a web-based information system that can be accessed by admins, employees, and customers.